Fundamental Study of Quantitative Evaluation of Radio Wave Output of Wireless Medical Telemetry Transmitters Operable in Medical Field (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: wireless medical telemetry transmitter; distance characteristics; free-space propagation model